Bone Marrow Aspirate in the Treatment of Chondral Injuries - Holton, James; Imam, Mohamed A.; Snow, Martin (Frontiers in Surgery, 2016)
The ability of mesenchymal stem cells (MSCs) to transdifferentiate into a desired cell lineage has captured the imagination of scientists and clinicians alike. The limited ability for chondrocytes to regenerate in chondral injuries has raised the concept of using MSCs to help regenerate and repair damaged tissue. The expansion of cells in a laboratory setting to be delivered back to the patient is too costly for clinical use in the present tough economic climate. This process is slow with due to the complexity of trying to imitate the natural environment and biological stimulation of chondral cell replication and proliferation. Bone marrow aspirate concentrate (BMAC) has the potential to provide an easily accessible and readily available source of MSCs with key growth factors that can be used in treating chondral injuries. This review summarizes the underlying basic science of MSCs and the therapeutic potential of BMAC.